A systematic literature review on applications of information and communication technologies and blockchain technologies for precision agriculture development - Liu, Wei; Shao, Xue-Feng; Wu, Chia-Huei; Qiao, Ping (Journal of cleaner production, 2021)
This review examines literature from 2011 to 2020 on information and communications technologies (ICTs) and blockchain technologies (BTs) in agriculture. To describe the status of the subjects and identify issues for future research, we utilized bibliometric and content analyses of leading journals. The main findings are: (1) ICT technique adoption is affected by application design and socio-demographic factors, while research in BTs in this area only focuses on application design factors; (2) ICTs and BTs have similar applications in agricultural production (information provision for efficient decisions and production improvement), logistics (tracing), and supply chain (trust-building); (3) ICT techniques are applied more to production improvement, while BTs focus more on using visibility, traceability, and automation to improve transparency and transaction efficiency in whole sectors; (4) in relation to consumption, ICTs focus on balancing supply and demand to achieve market stability, while BTs investigate effects on consumer purchasing decisions. Insights are also proposed for future research based on common challenges in the application of ICT and blockchain in agriculture in the following areas: (i) security and privacy protection; (ii) solutions for scalability and interoperability; (iii) solutions for high cost and high consumption, and demands for high knowledge in technology application; (iv) formulation of policies and regulations related to standard criteria for market stability. This review provides a basis for studying the combination of ICTs and BTs in agriculture and furthers the understanding of their usage by comparison; this has significant implications for technological development and agricultural sustainability.